Characterization of cleaning and disinfecting tasks and product use among hospital occupations. Issue 1 (28th October 2014) - Saito, Rena; Abbas Virji, M.; Henneberger, Paul K.; Humann, Michael J.; LeBouf, Ryan F.; Stanton, Marcia L.; Liang, Xiaoming; Stefaniak, Aleksandr B.
<x xml:space="preserve">Abstract</x> Background Healthcare workers have an elevated prevalence of asthma and related symptoms associated with the use of cleaning/disinfecting products. The objective of this study was to identify and characterize cleaning/disinfecting tasks and products used among hospital occupations. Methods Workers from 14 occupations at five hospitals were monitored for 216 shifts, and work tasks and products used were recorded at five‐minute intervals. The major chemical constituents of each product were identified from safety data sheets. Results Cleaning and disinfecting tasks were performed with a high frequency at least once per shift in many occupations. Medical equipment preparers, housekeepers, floor strippers/waxers, and endoscopy technicians spent on average 108–177 min/shift performing cleaning/disinfecting tasks. Many occupations used products containing amines and quaternary ammonium compounds for >100 min/shift. Conclusions This analysis demonstrates that many occupations besides housekeeping incur exposures to cleaning/disinfecting products, albeit for different durations and using products containing different chemicals. Am. J. Ind. Med. 58:101–111, 2015. © 2014 Wiley Periodicals, Inc.